2018
DOI: 10.1158/0008-5472.can-17-1724
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Chromatin Domains in Glioblastoma Reveal a Subtype-Specific Signature of Glioma Stem Cells

Abstract: Glioblastoma multiforme (GBM) can be clustered by gene expression into four main subtypes associated with prognosis and survival, but enhancers and other gene-regulatory elements have not yet been identified in primary tumors. Here, we profiled six histone modifications and binding as well as gene expression in primary gliomas and identified chromatin states that define distinct regulatory elements across the tumor genome. Enhancers in mesenchymal and classical tumor subtypes drove gene expression associated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…Therefore, PSAP may contribute to the invasion, migration and aggressiveness of mesenchymal GBM, and possibly in all types of GBM or glioma. GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PSAP may contribute to the invasion, migration and aggressiveness of mesenchymal GBM, and possibly in all types of GBM or glioma. GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Another repressive mark, H3K27me3, displayed a reduced domain size in GICs, which supports the conclusion that chromatin in these cells is in a more open and plastic stem cell‐like state. Furthermore, it is noted that deregulation of H3K27me3 was recently linked to the presence of bivalent chromatin domains in glioblastoma subtypes that pointed toward dedifferentiation into a more stem cell‐like phenotype …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is noted that deregulation of H3K27me3 was recently linked to the presence of bivalent chromatin domains in glioblastoma subtypes that pointed toward dedifferentiation into a more stem cell-like phenotype. 40 Since KDM enzymes can be competitively inhibited with α-ketoglutarate mimics like DMOG, 37,41 we evaluated the cellular response toward this compound. Remarkably, inhibition of NCH421k and NCH644 GICs with DMOG restored global H3K9me3 levels to that of the differentiated references, led to DNA damage and induced cell death specifically in the GIC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Reads were then counted using featureCounts and differential expression was calculated using DESeq2 (14,15). miRNA libraries were constructed from primary tumor samples derived as previously described (12). Reads mapping to mature miRNAs (miRBase v21) were then counted using a custom script.…”
Section: Rna-seq and Data Analysismentioning
confidence: 99%
“…To determine if PRC2 also regulated the DLK1-DIO3 locus-encoded miRNAs in primary brain tumors, we analyzed H3K27me3 ChIP-seq data that we had previously generated in primary tumors (12). We found H3K27me3 to be differentially enriched at this locus across multiple GBM (GBM1 and GBM2) and anaplastic astrocytoma (AA1 and AA2) tumor samples ( Fig.…”
mentioning
confidence: 99%